Early Growth Response of Capsicum frutescens L. (Ori 202 Variety) under Humic Acid Application in Cocopeat-Based Growing Media - Evan Vria Andesmora; Riko Aprianto; Wahilman Syahmi; Riza Julian Putra; Dede Amaliya (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2026)
Responses to humic acid (HA) are strongly influenced by plant genotype and cultivation conditions; however, information regarding HA application rates for bird’s eye chili (Capsicum frutescens L. cv. Ori 202) under container-based cultivation remains limited. This study evaluated the growth response of bird’s eye chili to HA applied at five concentrations in a completely randomized design consisting of H0 = 0, H1 = 2.5 mL L−1, H2 = 5 mL L−1, H3 = 7.5 mL L−1, and H4 = 10 mL L−1. Applications began seven days after planting and were repeated at seven-day intervals. Vegetative performance was assessed using biomass-related parameters, including plant height, leaf number, stem diameter, root length, root and shoot biomass, fresh and dry weights, and root-to-shoot ratio. Data were analyzed using analysis of variance followed by Duncan’s Multiple Range Test at α = 0.05. HA application significantly enhanced vegetative growth and biomass accumulation compared with the control treatment (p < 0.05). The H1 treatment (2.5 mL L−1) produced the highest total dry weight (1.94 g) and total fresh weight (17.82 g), indicating superior early biomass accumulation. Meanwhile, H2 (5 mL L−1) resulted in the greatest root length (13.43 cm). In contrast, the highest concentration (H4) did not provide growth benefits and performed similarly to or lower than the control. Under the experimental conditions, HA at 2.5 mL L−1 was the most effective treatment for promoting biomass accumulation in C. frutescens cv. Ori 202, although further validation under cultivation environments is still required to confirm its applicability.